1997
DOI: 10.1023/a:1026428918301
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for oral squamous cell carcinoma by tegafur and streptococcal agent OK-432 in combination with radiotherapy: Association of the therapeutic effect with differentiation and apoptosis in the cancer cells

Abstract: Twenty patients with oral squamous cell carcinoma having mainly stage II or III lesions without distant metastasis, were treated with tegafur and streptococcal agent, OK-432, in combination with radiotherapy. As a consequence, 16 cases among the treated 20 cases showed complete remission by this therapy alone. Especially, we have found that the squamous cell carcinoma arising in non-keratinizing oral epithelium rather than in keratinizing oral epithelium has better response to this therapy. Among the 16 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…We have also reported that OK-432-based immunotherapy exhibits a marked antitumor effect in patients with oral squamous cell carcinomas (4,5). It has been reported that OK-432 induces interleukin (IL)-12 and polarizes the T-cell response to a helper T-cell 1 (Th1)-dominant state in mice (6), that local injection of OK-432 augments the Th1-type T-cell response of tumor-draining lymph node cells (7), and that OK-432 induces lymphokine-activated killer cells that exhibit higher cytotoxic activities and have a different phenotype from the lymphokine-activated killer cells induced by IL-2 (8).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have also reported that OK-432-based immunotherapy exhibits a marked antitumor effect in patients with oral squamous cell carcinomas (4,5). It has been reported that OK-432 induces interleukin (IL)-12 and polarizes the T-cell response to a helper T-cell 1 (Th1)-dominant state in mice (6), that local injection of OK-432 augments the Th1-type T-cell response of tumor-draining lymph node cells (7), and that OK-432 induces lymphokine-activated killer cells that exhibit higher cytotoxic activities and have a different phenotype from the lymphokine-activated killer cells induced by IL-2 (8).…”
Section: Introductionmentioning
confidence: 83%
“…Briefly, mouse bonemarrow cells were harvested from the femur and tibia of sacrificed mice. Contaminating erythrocytes were lysed with 0.83 M NH 4 Cl buffer, and lymphocytes were depleted with a mixture of antibodies (RL-172, anti-CD4; TIB-105, anti-CD8; TIB-140, anti-B220; all from the American Type Culture Collection, Manassas, VA) and rabbit complement (Accurate Chemical and Scientific Corp., Westbury, NY). These cells were cultured overnight in RPMI 1640 containing 10% heat-inactivated FBS to remove the adherent macrophages, and then nonadherent cells were placed in fresh culture medium supplemented with 1000 units/ml recombinant murine GM-CSF (PeproTech, London, England) and recombinant murine IL-4 (PeproTech) for 6 days to induce iDCs.…”
Section: Introductionmentioning
confidence: 99%
“…Biopsy specimens and metastatic lymph nodes were obtained from 1990 to 1999 at the Second Department of Oral and Maxillofacial Surgery, Tokushima University Dental Hospital. All the patients selected in this study were primary treated by radiation, chemotherapy, and immunotherapy, as described previously (52). Immunohistochemistry was done with anti-CXCR4 monoclonal antibody (12G5; BioSource International) or anti -SDF-1a monoclonal antibody (R&D Systems, Inc.) as described previously (13).…”
Section: Patients and Immunohistochemistrymentioning
confidence: 99%
“…OK-432 is an immunomodulatory agent prepared from an avirulent human strain of Streptococcus pyogenes. It has been shown to induce various cytokines, especially Th1 cytokines (Saito et al, 1982;Yamamoto et al, 1986;Yang et al, 1992) and to upregulate both perforin (Kataoka et al, 1991) and Fas ligand expression (Toda et al, 1996;Sato et al, 1997) of immune cells. In accordance with these findings, OK-432 is also known to enhance or activate the cytotoxic activity of various effector cells (Ishii et al, 1976;Uchida and Micksha, 1983), which may be responsible for its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these findings, OK-432 is also known to enhance or activate the cytotoxic activity of various effector cells (Ishii et al, 1976;Uchida and Micksha, 1983), which may be responsible for its therapeutic effect. The augmentation of perforin (Kataoka et al, 1991), induction of IL-2 and IFN-γ, and the upregulation of Fas ligand (Toda et al, 1996;Sato et al, 1997) by OK-432 may play a major role in promoting anti-tumour necrotic and apoptotic effects of immune cells like NK cells, LAK cells, CTL (Kagii et al, 1994;Lowin et al, 1994;Lin et al, 1995;Frost et al, 1997), and TILs. These such biological activity of OK-432 are thought to occur at the tumour site in the case of intratumoral injection of OK-432.…”
Section: Discussionmentioning
confidence: 99%